Assessment of Left Atrial Function after Percutaneous Closure of Patent Foramen Ovale. Issue 7 (24th January 2013) - Vavuranakis, Manolis; Kavouras, Charalampos; Vlasseros, Ioannis; Aggeli, Constantina; Felekos, Ioannis; Vrachatis, Dimitrios A.; Stefanadis, Christodoulos
<x xml:space="preserve">Abstract</x> Background Τhe influence of atrial septal occluders in left atrial (LA) function after percutaneous closure of patent foramen ovale (PFO) has not been thoroughly studied. Methods Twenty‐five patients (mean age 40.7 ± 12 years) undergoing percutaneous PFO closure were enrolled in this study. Transthoracic echocardiogram (TTE) was performed 3 and 6 months before the procedure. Volumetric indices (active emptying fraction: LA AEF, expansion index: LA EI, and passive emptying fraction: LA PEF), strain and strain rate (SR), were calculated during the contractile, reservoir, and conduit LA phases for the lateral, anterior, and inferior LA walls with TTE. Results After 3 months, a decrease in the SR of the LA anterior wall was observed (from 2.12 ± 0.22 to 1.66 ± 0.26, P < 0.045), while the LA lateral wall strain was found to be increased (from 0.708 ± 0.15 to 0.783 ± 0.159, P < 0.001). Moreover, simultaneously LA AEF was greater compared with baseline (from 31.0 ± 1.6 to 34.0 ± 1.6, P < 0.004). However, all these alterations reversed at 6 months. Conclusions Segmental LA function is altered transiently after percutaneous PFO closure with a septal occlude. The LA anterior wall SR decreases, while the lateral wall strain increases. The impact of these alterations needs further clarification.